2018
DOI: 10.1038/s41598-018-27002-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced carbon-sulfur cycling in the sediments of Arabian Sea oxygen minimum zone center

Abstract: Biogeochemistry of oxygen minimum zone (OMZ) sediments, which are characterized by high input of labile organic matter, have crucial bearings on the benthic biota, gas and metal fluxes across the sediment-water interface, and carbon-sulfur cycling. Here we couple pore-fluid chemistry and comprehensive microbial diversity data to reveal the sedimentary carbon-sulfur cycle across a water-depth transect covering the entire thickness of eastern Arabian Sea OMZ, off the west coast of India. Geochemical data show re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(124 citation statements)
references
References 94 publications
(82 reference statements)
4
120
1
Order By: Relevance
“…The corresponding sedimentary δ 13 C org value, from oxygenated bottom waters at 1445 m depth, was, however, more enriched (-20.8‰; Wakeham & McNichol, 2014). Fernandes et al (2018) detected similar, though less pronounced, trends in sediments collected from the Pakistan margin. An increase in δ 13 C org with enhanced degradation, i.e.…”
Section: Origin Of Sedimentary Organic Matter (Som)mentioning
confidence: 80%
See 1 more Smart Citation
“…The corresponding sedimentary δ 13 C org value, from oxygenated bottom waters at 1445 m depth, was, however, more enriched (-20.8‰; Wakeham & McNichol, 2014). Fernandes et al (2018) detected similar, though less pronounced, trends in sediments collected from the Pakistan margin. An increase in δ 13 C org with enhanced degradation, i.e.…”
Section: Origin Of Sedimentary Organic Matter (Som)mentioning
confidence: 80%
“…Further, BHT and BHT' are also present in the surface of the oxic sediments (P1800), in proportions similar to the anoxic sediments at P900. Even if anammox growth was too slow for labelling to take effect, substantial sedimentary production would have resulted in a decreasing δ 13 C value of BHT' in the unamended cores, as DIC gradually becomes more 13 C depleted with sediment depth (Fernandes et al, ), but this is not observed (Figure b and c). Collectively, these data support the idea that the vast majority of BHT' is derived from anammox bacteria living in the OMZ of the water column, and that BHT also has a predominant pelagic origin with limited sedimentary production.…”
Section: Discussionmentioning
confidence: 99%
“…To determine their stable sulfur isotope ratios, dried and homogenized BaSO 4 or Ag 2 S precipitates were mixed with V 2 O 5 , flash combusted at 1,150°C in an EA1112 elemental analyzer (Thermo Fisher Scientific), and then analyzed using a Thermo Delta V plus continuous flow isotope ratio mass spectrometer (Thermo Fisher Scientific) (Fernandes et al, 2018). All results were reported in standard delta notation (δ 34 S) 210 as per mil (‰) deviations from the VCDT (Vienna Canyon Diablo Troilite), with reproducibility of ± 0.3 ‰.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…240 2.7. Assessment of metataxonomic diversity within the Lotus Pond-Rulang ecosystem V3 regions of all bacterial/archaeal 16S rRNA genes present in an environmental DNA preparation were PCR amplified using Bacteria-/Archaea-specific universal oligonucleotides, following the fusion primer protocol described previously (Ghosh et al, 2015;Roy et al, 2016;Fernandes et al, 2018). Amplification was carried out using a 16S forward primer prefixed with an Ion Torrent adapter and a unique sample-specific barcode or 245 multiplex identifier in the following 5′ to 3′ organization: (a) a 26-mer A-linker followed by a 4-mer A-linker key common for all sample-specific primers (see bases in bold fonts in the sequences given below), (b) a 10mer barcode unique to each sample-specific primer, which is followed by a common 3-mer barcode adaptor (all denoted as stars in the sequences below), and then (c) the relevant domain-specific universal forward primer in its 5′ to 3′ direction (see underlined bases in the sequences given below).…”
Section: Preparation Of Total Environmental Dna From Water-samplesmentioning
confidence: 99%
“…Community structures and functions of tetrathionate-forming, oxidizing, and respiring, microorganisms were revealed (via metagenomics, metatranscriptomics and pure-culture isolation) along two ~3-m-long sediment cores (Fernandes et al, 2018) collected from 530 and 580 meters below the sea level (mbsl); the microbial ecology was then considered in the context of the in situ geochemistry, and implications were inferred for the in situ sulfur cycle. 70 2 Materials and methods…”
mentioning
confidence: 99%